Extended applications of the reamer-irrigator-aspirator (RIA) system. (June 2017) - Dehghan, Niloofar; Schemitsch, Emil H.
Abstract: While the RIA system was initially designed for reaming and clearing the femoral canal contents in preparation for femoral nailing, it has since been used in various other applications in the field of orthopaedic surgery. The RIA is an ideal device for accessing large quantities of autogenous bone graft, to be used in the treatment of nonunions, segmental bone loss, or arthrodesis. The RIA has also been used for treatment of intramedullary infections and osteomyelitis, as well as intramedullary nailing of long bones with metastatic lesions, as it allows for clearing the canal of infectious/tumour burden, and lowers the risk of dissemination into the soft tissues and systemic circulation. There is also some limited evidence that the RIA may be used for clearing the femoral/tibial canal of cement debris. Despite multiple applications, the use of RIA has a risk of eccentric reaming and iatrogenic fractures. RIA is also a costly procedure, and its routine use may not be advantageous in the setting of limited health care resources.